2021
DOI: 10.1007/s10899-021-09998-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Voluntary Self-exclusion Reinstatement Tutorial for Problem Gamblers

Abstract: Voluntary self-exclusion programs allow gamblers to voluntarily be denied access to gambling venues for an agreed upon period. Many people who self-exclude decide to return to gambling venues after the exclusion period has ended, however people who reinstate may be at risk for the recurrence of gambling problems. This study was designed to determine the efficacy of a tutorial created with the intent of reducing the risk of harm to those who reinstate. People who wished to be reinstated were asked to complete a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In spite of the protective role of self-exclusion, research has found that the greater the accessibility of gambling or the ease of evading self-exclusion measures, the less harm minimization of the gambling problem will be ( Hayer & Meyer, 2011 ; Strohäker & Becker, 2018 ). This may be related with what some studies have reported, that the longer a person spends in a gambling establishment and the greater the accessibility is, the more likely they are to self-exclude several times, since some people return to gambling venues at the end of their self-exclusion period ( Sharman et al., 2019 ; Strohäker & Becker, 2018 ; Turner, Shi, Robinson, McAvoy, & Sanchez, 2021 ).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…In spite of the protective role of self-exclusion, research has found that the greater the accessibility of gambling or the ease of evading self-exclusion measures, the less harm minimization of the gambling problem will be ( Hayer & Meyer, 2011 ; Strohäker & Becker, 2018 ). This may be related with what some studies have reported, that the longer a person spends in a gambling establishment and the greater the accessibility is, the more likely they are to self-exclude several times, since some people return to gambling venues at the end of their self-exclusion period ( Sharman et al., 2019 ; Strohäker & Becker, 2018 ; Turner, Shi, Robinson, McAvoy, & Sanchez, 2021 ).…”
Section: Introductionmentioning
confidence: 72%
“…Therefore, more effective relapse methods based on the profiles of people who resort to self-exclusion are needed to add to psychological treatments ( Sharman et al., 2019 ; Strohäker & Becker, 2018 ; Turner et al., 2021 ). In addition to that, having a better knowledge of the socio-demographic, psychopathological, personality and gambling behavior profiles of people who ask for self-exclusion before seeking professional treatment can contribute to designing prevention programs that are more oriented towards the target population (people with gambling problems who are unaware of this protection strategy), and to strengthen the decision of those that have already self-excluded.…”
Section: Introductionmentioning
confidence: 99%
“…Recommendations have been advanced, tested, and in some instances implemented to structurally enhance self-exclusion interventions, with new and emerging technology as the primary source of innovation ( Håkansson and Henzel, 2020 ; Ipsos MORI Public Affairs, 2020 ; Pickering et al, 2018 ; Turner et al, 2021 ). Certain contemporary programs allow individuals to self-exclude from multiple gambling venues under a single registration process that uses a centralised online database to collect and store client information ( Hing and Nuske, 2012 ; Pickering et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%